2021
DOI: 10.2478/ausfm-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Soundtrack of the Sinister Trailer

Abstract: In this article, I analyse the soundtrack of the green band trailer for Sinister (Scott Derrickson, 2012), combining quantitative methods to analyse the soundtrack with formal analysis. I show that, even though Sinister is a narrative about a demon who lives in images, the horror in the soundtrack of this trailer is articulated through the sound design. I describe the structure of the soundtrack and analyse the distribution and organisation of dialogue, the use of different types of sound effects to create a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Brotto (2013, 155) observed that computational methods for exploring film style lacked a method for analyzing sound. Despite an abundance of freely available audio analysis tools developed in the fields of bioacoustics, soundscape ecology, and computational music analysis, few (Ma et al 2021;Moncrieff, Dorai, and Venkatesh 2002;Pfeiffer and Srinivasan 2002;Redfern 2020aRedfern , 2020bRedfern , 2021 have attempted to apply these technologies to the analysis of motion picture soundtracks.…”
mentioning
confidence: 99%
“…Brotto (2013, 155) observed that computational methods for exploring film style lacked a method for analyzing sound. Despite an abundance of freely available audio analysis tools developed in the fields of bioacoustics, soundscape ecology, and computational music analysis, few (Ma et al 2021;Moncrieff, Dorai, and Venkatesh 2002;Pfeiffer and Srinivasan 2002;Redfern 2020aRedfern , 2020bRedfern , 2021 have attempted to apply these technologies to the analysis of motion picture soundtracks.…”
mentioning
confidence: 99%